2008
DOI: 10.1016/s0140-6736(08)60167-1
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian cancer and oral contraceptives: collaborative reanalysis of data from 45 epidemiological studies including 23 257 women with ovarian cancer and 87 303 controls

Abstract: SummaryBackground Oral contraceptives were introduced almost 50 years ago, and over 100 million women currently use them. Oral contraceptives can reduce the risk of ovarian cancer, but the eventual public-health eff ects of this reduction will depend on how long the protection lasts after use ceases. We aimed to assess these eff ects.Methods Individual data for 23 257 women with ovarian cancer (cases) and 87 303 without ovarian cancer (controls) from 45 epidemiological studies in 21 countries were checked and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
186
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 670 publications
(206 citation statements)
references
References 55 publications
9
186
1
2
Order By: Relevance
“…However, today’s formulations contain much lower hormone doses than did the original pills. Typical estrogen doses in OCs prescribed in the 1960s, 1970s, and 1980s (and beyond) were ≥100, ~50, and ≤30 μg, respectively (7). Today, about two-thirds of current OC users in the U.S. take pills containing 30-<50 μg of ethinyl estradiol (low-dose OCs), one-third take pills containing 20 μg (very low dose OCs), and 2% take high-dose pills containing 50 μg (3).…”
Section: Oral Contraceptivesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, today’s formulations contain much lower hormone doses than did the original pills. Typical estrogen doses in OCs prescribed in the 1960s, 1970s, and 1980s (and beyond) were ≥100, ~50, and ≤30 μg, respectively (7). Today, about two-thirds of current OC users in the U.S. take pills containing 30-<50 μg of ethinyl estradiol (low-dose OCs), one-third take pills containing 20 μg (very low dose OCs), and 2% take high-dose pills containing 50 μg (3).…”
Section: Oral Contraceptivesmentioning
confidence: 99%
“…In a 2008 meta-analysis of 45 case-control and cohort studies, the proportional risk reductions in ovarian cancer incidence per 5 years of OC use were 29% (23-34%), 19% (14-24%), and 15% (9-21%) for use that had stopped <10, 10-19, and 20-29 years prior (7). Despite falling OC estrogen doses during the 1960s, 1970s, and 1980s, the strength of the risk reductions did not vary across calendar time.…”
Section: Oral Contraceptivesmentioning
confidence: 99%
“…The COCP is an extremely effective form of contraception if taken correctly, and it also has several health benefits, including a reduction in the risk of ovarian [20], endometrial [21] and colorectal cancer [22]. …”
Section: The Cocpmentioning
confidence: 99%
“…Similarly, in a meta-analysis assessing cancer risk after exposure to sex hormones [4], no risk increase for ovarian cancer was found after use of COCs. Previous studies have actually shown a decreased risk of ovarian cancer after use of oral contraceptives [15]. For cervical cancer, a small risk increase was shown for present users.…”
Section: Discussionmentioning
confidence: 77%